Mitochondrial Dynamin-Related Protein 1 (DRP1) translocation in response to cerebral glucose is impaired in a rat model of early alteration in hypothalamic glucose sensing - Lucie Desmoulins; Chloé Chrétien; Romain Paccoud; Stephan Collins; Céline Cruciani-Guglielmacci; Anne Galinier; Fabienne Liénard; Aurore Quinault; Sylvie Grall; Camille Allard; Claire Fenech; Lionel Carneiro; et al. (Elsevier, 2019)
Objective: Hypothalamic glucose sensing (HGS) initiates insulin secretion (IS) via a vagal control, participating in energy homeostasis. This requires mitochondrial reactive oxygen species (mROS) signaling, dependent on mitochondrial fission, as shown by invalidation of the hypothalamic DRP1 protein. Here, our objectives were to determine whether a model with a HGS defect induced by a short, high fat-high sucrose (HFHS) diet in rats affected the fission machinery and mROS signaling within the mediobasal hypothalamus (MBH). Methods: Rats fed a HFHS diet for 3 weeks were compared with animals fed a normal chow. Both in vitro (calcium imaging) and in vivo (vagal nerve activity recordings) experiments to measure the electrical activity of isolated MBH gluco-sensitive neurons in response to increased glucose level were performed. In parallel, insulin secretion to a direct glucose stimulus in isolated islets vs. insulin secretion resulting from brain glucose stimulation was evaluated. Intra-carotid glucose load-induced hypothalamic DRP1 translocation to mitochondria and mROS (H2O2) production were assessed in both groups. Finally, compound C was intracerebroventricularly injected to block the proposed AMPK-inhibited DRP1 translocation in the MBH to reverse the phenotype of HFHS fed animals. Results: Rats fed a HFHS diet displayed a decreased HGS-induced IS. Responses of MBH neurons to glucose exhibited an alteration of their electrical activity, whereas glucose-induced insulin secretion in isolated islets was not affected. These MBH defects correlated with a decreased ROS signaling and glucose-induced translocation of the fission protein DRP1, as the vagal activity was altered. AMPK-induced inhibition of DRP1 translocation increased in this model, but its reversal through the injection of the compound C, an AMPK inhibitor, failed to restore HGS-induced IS. Conclusions: A hypothalamic alteration of DRP1-induced fission and mROS signaling in response to glucose was observed in HGS-induced IS of rats exposed to a 3 week HFHS diet. Early hypothalamic modifications of the neuronal activity could participate in a primary defect of the control of IS and ultimately, the development of diabetes. Keywords: Hypothalamus, Glucose sensing, Mitochondria, ROS signaling, Mitochondrial fission, DRP1